Exercise-induced mitochondrial biogenesis in muscle 1 - Hood, David (Henry Stewart Talks, 2018)
Introduction to skeletal muscle fiber types, Mitochondrial morphology in muscle fiber types, Mitochondrial adaptations to exercise training, Mitochondrial content, physical activity & aging, Signaling to mitochondrial biogenesis, Endurance performance & mitochondria content